MODERATE MUSLIM BY BAHA’I RELIGIOUS COMMUNITY: A CASE STUDY IN PATI REGENCY IN CENTRAL JAVA - Moh Rosyid (Al Qalam, 2020)
This article based on research carried out in Januari-Juni 2019 among the Baha'i religious community in the village of Cebolek Kidul, Pati Regency, Central Java. Data of this article were collected through interviews, observations, documentations, and focus group discussion by qualitative approach. In Cebolek, there are 27 people of 9 families. Baha’i is an independent religion that was first known in Persia in 1840s and came to Indonesia in 1870 brought by joint medical experts in the UN program so that the villagers of Cebolek knew the Baha’i teachings through the Baha’is. In the era of the Old Order and the New Order, Baha'i organizations were banned by the state so they sought protection from NGOs and government institutions even though their efforts were unsuccessful. In the era of President Gus Dur, the president revoked the ban, although negative views by the public and the government still exist today. In the midst of their life, the Baha'is in Cebolek Village have now been responded positively by Nahdliyin (NU) in the form of (1) tying the tomb and attending the funeral when the Baha'i died, (2) praying (reading tahlil) at the house of Baha'i after the funeral. The Baha’is feel comfortable because of the following reasons: (1) NU embodies the teachings of ahlussunnah wal jamaah, (2) there are no 'defenders of Islam' in the Baha'i, (3) a way of thinking figur NU is moderat, (4) Baha'is always ready to give the construction of public facilities and places of worship for the NU. Baha'i people who have funds and land, provide capital to their neighbors (NU) who wish to raise cattle, work on rice fields and shrimp farms with a profit sharing system. Good interaction between the financiers and the capitalists creates positive interactions in the neighborhood. Convenience was preserved because the Baha'i: (a) began to do good with NU in the cultural forum of rural residents accommodated by NU, (b) together with the Baha'i institution, opening themselves to the public for their teachings, and (c) no longer complaining about their problems to NGOs and the government.